(untitled) (Антропологический форум / Forum for Anthropology and Culture, 2021)
In ethnographic research into material culture, things are described primarily as signs of social phenomena, while the things themselves remain in the background. Even in the case of ‘object-orientated’ research in the museum, the material object appears as an element of a taxonomy, or as a model of the techniques of making and being in a local tradition, or as a representative of the cultural contexts from which it was taken. The very fact that things are preserved in museums in the format of a collection casts a shadow over a thing’s uniqueness, since its singular nature does not fit into the collection as a whole, in that every object is indeed a ‘world of individuality’. The article examines ways in which museum ethnography might escape from the parameters of its native anonymous and depersonalising discourse. A ‘biographical’ focus is proposed as an alternative to this, allowing objects’ subjectivity and individuality to be seen. A thing’s uniqueness is manifested not only in its biography, but also in its physical nature: its material, form, construction, finish, colour, weight, smell, etc. Close attention on the part of museum ethnography to particular people and the unique objects associated with them allows an elucidation of those details and peculiarities without which a culture as a whole cannot be understood.